Risk factors for symptomatic anastomotic postoperative recurrence following ileo‐colic resection in Crohn's disease. (3rd February 2021) - Navaratne, Lalin; Hurndall, Katherine‐Helen; Richardson, Daniel M.; Stephenson, Robert; Power, Niall; Gillott, Holly; Ruiz Sánchez, Susana; Khodatars, Kuresh; Chan, Christopher L. H.
Abstract: Aim: Crohn's disease is a chronic inflammatory bowel disease characterized by alternating periods of exacerbation and remission. Surgical resection is not curative and postoperative recurrence (POR) remains a challenge in these patients. The aim of this study was to identify clinical variables that influence the risk of symptomatic anastomotic POR in patients with ileo‐colonic Crohn's disease. Method: A retrospective study of Crohn's disease patients who had undergone ileo‐colic resection between January 2014 and December 2018 was performed. For each patient, data including demographic information, Crohn's disease clinical setting, preoperative radiological data, operative and histological data, pre‐ and postoperative medication history and postoperative clinical course, including recurrence of disease, were extracted. Symptomatic anastomotic POR was defined as symptoms of Crohn's disease in the presence of confirmed anastomotic POR (endoscopic and/or radiological POR). Results: For the study period, 104 patients were eligible and included for analysis. The cumulative probability of symptomatic anastomotic POR was 14%, 30%, 42%, 50% and 50% at 1, 2, 3, 4 and 5 years, respectively. Two clinical variables on multivariate analysis were associated with increased risk of symptomatic anastomotic POR, namely age <17 years at diagnosis [hazard ratio (HR) 2.17, p  = 0.019] and gastrointestinal involvement (extent) >30 cm (HR 1.85, p  = 0.048). Conclusion: This study describes the natural history of POR after ileo‐colic resection for Crohn's disease, as defined by endoscopic, radiological and clinical outcomes. Age <17 years at diagnosis and gastrointestinal involvement (extent) >30 cm were independent risk factors for symptomatic anastomotic POR.